2013
DOI: 10.1111/php.12186
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Photosensitizer Penetration into Artificial Caries Lesions in Dentin Measured by the Confocal Raman Microscopy

Abstract: This study utilized the confocal Raman microspectroscopy (CRM) technique for the first time to investigate the degree of the penetration of toluidine blue-orto (TBO) in artificial caries lesions produced by two distinct caries-inducing models. The dentin specimens (n = 10) were divided into three groups: control, in vitro and in situ. Thereafter, the lesion depth and the demineralization level were evaluated by cross-sectional microhardness (CSMH). CRM mapping across the dentin surface was assessed after the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Tissue-substrate related factors such as the ability of the photosensitizer to penetrate dentinal tubules to reach the bacteria in appropriate site and the requirement that light should be delivered to the microorganism with appropriated propagation in dentin tissue are considerable obstacles to the clinical use of PACT in caries lesions [32,33]. Dentin represents a unique substrate, in which the dye need to penetrate in demineralized area to reach the disinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue-substrate related factors such as the ability of the photosensitizer to penetrate dentinal tubules to reach the bacteria in appropriate site and the requirement that light should be delivered to the microorganism with appropriated propagation in dentin tissue are considerable obstacles to the clinical use of PACT in caries lesions [32,33]. Dentin represents a unique substrate, in which the dye need to penetrate in demineralized area to reach the disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study [32] evaluated the degree of the penetration of toluidine blue orto (TBO) in artificial caries lesions, in which the rate of TBO penetration was detected up to about ∼50 μm. However, PACT aim to reduce the bacterial core in caries-affected dentin and not reach the tissue sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the penetration of toluidine blue and methylene blue in healthy dentin are, respectively, 130 and 190 µm, 26 and this penetration is even smaller in the carious dentin, only 52.6 µm below the surface. 27 Therefore, the altered structure of the carious dentin may not allow adequate penetration of the photosensitizer 28,14 and its interaction with microorganisms such as the ones in the mutans group, which have been observed in dental tubules at depths of 200 µm or more from the dentinal surface. 29 The study of new parameters such as the type and concentration of the dyes may give new perspectives for an antimicrobial effect of PDT.…”
mentioning
confidence: 99%
“…In our study, we used the MB photosensitizer, so we supposed a large penetration, however, in carious dentin, the depth that the photosensitizer can penetrate is still uncertain because the photosensitizer may have difficulty dispersing in the inner layers of carious tissue, and the light may have difficulty being fully transmitted . The ability of the photosensitizer to penetrate the dentin tubules, to reach the bacteria in deeper stages and the requirement that the light be administered with appropriate propagation in dentin tissue represent obstacles for the clinical use of aPDT in deep carious lesions , since the penetration is limited, and may vary according to the solubility, concentration and size of the dye particle . Despite this, the study of Melo et al .…”
Section: Discussionmentioning
confidence: 99%